INDOMARET VS ALFAMART : THE BATTLE FOR STORE ATMOSPHERE SUPREMACY - Wardana, M. Azka Kesuma; Octavini, Nanda Andreas; Nurbaiti, Seni (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Indomaret and Alfamart, two retail giants in Indonesia, compete fiercely for market share. This study focuses on the Competition in the in-store experience, known as